Mixed member proportional meets alternative vote: rethinking American politics - Waldner, Niklas (Austrian journal of political science, 2024)
In this paper I begin with the premise of a two-pronged crisis of representative democracy in the United States. In response to this two-pronged crisis, I suggest merging the alternative vote (AV) and mixed member proportional (MMP) into a single electoral system. I argue that the resulting necessity for legislative and electoral coalition-building, as well as the more favourable conditions for it, address the core problems facing American democracy. In reviewing this argument in more detail, however, it becomes apparent that only some of the assumptions required for it to hold are supported by existing empirical research, while others tread on new ground. These research gaps illustrate promising avenues for future research.
Im Web of Science ist der DOI fälschlich als 10.15203/ozp.4117.vol52iss4 angegeben
Gesehen am 21.02.2024